Umpasa In The Giving Of Ulos In Traditional Batak Toba Ceremonies: Ananthropolinguistic Study - Erica Yulia Citra Sitorus; Robert Sibarani; Sibarani, Jekmen Sinulingga; Warisman Sinaga; Ramlan Damanik (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2024)
This research is entitled Umpasa in Giving Ulos at the Toba Batak Traditional Ceremony: An Anthropolinguistic Study. This research aims to describe the performance of umpasa in giving ulos at the Toba Batak traditional ceremony, the indexicality of umpasa in giving ulos at the Toba Batak traditional ceremony, and the participation of umpasa in giving ulos at the Toba Batak traditional ceremony. The theory used to analyze the data is anthropolinguistic theory proposed by Alessandro Duranti. The method used in this research is descriptive qualitative method of interactive model. The results obtained from this study are the performance of umpasa in giving ulos at the traditional birth ceremony, namely: (1) mangirdak/mambosuri, (2) mangharoani, (3) mebat/paebathon, (4) tardidi. Performances in the traditional wedding ceremony, namely: (1) marhusip/marhori-hori dinding, (2) marhata sinamot, (3) martumpol, (4) marsibuhai-sibuhai, (5) manjalo pasu-pasu parbogashon, (6) marunjuk, (7) paulak une, and (8) manikkir tangga. Performances in the traditional death ceremony, namely: (1) martonggo raja, (2) sarimatua, and (3) saurmatua. Indexicality in the Toba Batak traditional ceremony, namely, (1) umpasa, (2) ulos. Participants of umpasa in giving ulos at the Toba Batak traditional ceremony are Dalihan Natolu (1) hula-hula, (2) dongan tubu, and (3) boru.